Effectiveness of KPAI's Role in Legal Protection of Children as Victims of Bullying Crime - Wibawa Putra, Made Fajar Ari; Rusmini Gorda, A.A.A.Ngurah Tini (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
Bullying is frequently encountered, particularly within school environments. In response to this issue, The Indonesian Child Protection Commission (KPAI) was established to protect the interests of children and prevent violence against them. This study aims to examine the effectiveness of the Indonesian Child Protection Commission in safeguarding the rights of children who are victims of bullying crimes, and the legal protections provided for children as victims of such crimes. The empirical legal method was employed in this research, utilizing both primary and secondary data sources. Data collection techniques included interviews and literature studies, with qualitative descriptive data analysis. In the discussion of this research, the author utilizes the theories of legal effectiveness, legal protection, and the principle of lex specialis derogate legi generalis. The findings indicate that the Indonesian Child Protection Commission has effectively fulfilled its duties, as evidenced by a significant decrease in reported cases from 2021 to 2023. The role of the Indonesian Child Protection Commission, in collaboration with other institutions such as the Commission for the Protection of Children in the Region (KPPAD) and UPTD PPA, involves providing protection for children victimized by bullying through supervision, legal assistance, and psychological support.